Romancing the Camp: Genres of Holocaust Memory on the Story-Sharing Website Wattpad. Issue 2 (4th May 2018) - Benzaquen-Gautier, Stéphanie
ABSTRACT: The story-sharing website for amateur and professional writers Wattpad offers over a thousand stories about the Holocaust. Most are romances revolving around the same plot, the impossible love of a Jewish woman and a Nazi man. This article proposes to take a closer look at this 'bad writing, ' as scholar Berel Lang describes sentimental and cliché literature about the Holocaust. The stories on Wattpad raise many questions about the transmission of Holocaust memory through literature in the post-survivor and digital age. To what extent do these stories qualify as Holocaust writing? What role does the Holocaust as historical event play in these texts? What do the stories say about the popular representations through which Holocaust memory is passed down to younger generations? To answer these questions, the article examines a set of 65 stories selected for their size, popularity, and plot. Drawing on studies of romantic literature, Holocaust literature scholarship (including children's literature), and media studies, it explores the narrative structures, characters, and settings of the stories and tries to understand their impact on readers in terms of gender construction and confrontation with the past. Then, the article analyzes the relation of history, fiction, and writing that materializes in these Holocaust romances, and the specific environment provided by the online platform for the formation of communities around questions of writing, popular culture, and emotions. Following Lang's suggestion that bad writing may also have 'good effects, ' the article positively assesses the impact of the Holocaust texts emerging from digital participatory culture.